Close Homolog of L1 Deficiency Exacerbated Intestinal Epithelial Barrier Function in Mouse Model of Dextran Sulfate Sodium-Induced Colitis - Han, Ying; Wang, Xiaomeng; Cheng, Xiang; Zhao, Ming; Zhao, Tong; Guo, Liang; Liu, Dan; Wu, Kuiwu; Fan, Ming; Shi, Ming; Zhu, Lingling (Frontiers in Physiology, 2020)
The cell adhesion molecule CHL1, which belongs to the immunoglobulin superfamily, functions in a variety of physiological and pathological processes, including neural development, tissue injury and repair. We previously found that the loss of CHL1 exacerbated the DSS-induced colitis in mice. In the present study, we further addressed the role of CHL1 in mouse model of DSS-induced colitis and its’ potential mechanism. Colon tissues were collected from CHL1+/+, CHL1+/- and CHL1-/- mice after DSS induction to investigate the effects of CHL1 on the development of colitis. The data showed that CHL1 was expressed in intestine tissue, and expression of CHL1 was increased by DSS-induced inflammation. CHL1 deficiency induced more pronounced colitis features, exacerbated inflammation and damage to colonic tissues in DSS-induced mice. Moreover, colonic tissues of CHL1-/- mice showed a marked increase in neutrophil and macrophage infiltration, be accompanied by more severe damage to intestinal epithelial cells and higher FITC leakage. Our results revealed deficiency of CHL1 exacerbated DSS-induced colitis, and this pathogenesis was potentially mediated by disruption of intestinal barrier integrity, indicating that CHL1 may be an attractive therapeutic target for inflammatory bowel diseases (IBD) in mice.